Epidemiology study of cardiac arrest in the Fokidas geographical region - Karnava, Thaleia; Karanasiou, Eleni Apostolos; Rizothanasi, Konstantina (International Journal Of Community Medicine And Public Health, 2021)
Background: Cardiac arrest is a challenge for the healthcare professionals in the community, as there is a strong request for timely and specialized treatment by well-trained rescission purpose of this research is to present the epidemiology of cardiac arrest in the geographical region of Fokida. Methods: This is a retrospective study for the elaboration of which records from the Amfissas general hospital were used. With permission of the scientific committee of the hospital, the study started in March of 2017 until February 2018. The research was based on 85 cases of cardiac arrest that occurred from 2010 to 2015 (6 years overall). Results: According to the study it was found that the average age of the patients has been 69, 18 (9.40) years old. The outcome of CPR has been successful in 29, 4% of cases (25 patients). The incidents of cardiac arrest have quadrupled during the research period, and from 15/100,000 population in 2010 they reached 60/100,000 in 2015. In the age group of 50 to 59 years old, there has been an outcome for the 42% of the occurred incidents, whilst there has been a reduction of 7,7 % in the age group over 80 years old, that is this is a statistically significant difference (X2=4.697, p = 0.030). At the same time, co-morbidity burdened the prognosis. In all cases the CPR started within the hospital. Conclusions: There has been a significant increase in the incidents of cardiac arrest in recent years, and the success rates are satisfactory. Organizational weaknesses do not allow the early initiation of CPR before the patient arrives at the hospital.